Tourists’ Perceptions of Short-Term Rental Regulation and Destination Loyalty in Bali: The Mediating Roles of Accommodation Value and Governance Trust - I Wayan Kartimin; I Made Gede Darma Susila; Putu Guntur Pramana Putra (Centre of Excellence in Tourism Udayana University, 2026)
Short-term rental (STR) regulation has been widely discussed in relation to housing pressure, platform governance, and neighbourhood externalities, yet less is known about how tourists interpret such regulation in resort destinations. This study examines whether tourists’ perceptions of regulatory fairness, enforcement efficacy, and policy sustainability are associated with accommodation value, governance trust, and destination loyalty in Bali. A quantitative cross-sectional survey was conducted with 500 international tourists across Bali’s main tourist corridors and spillover zones between January and August 2025. The data were analysed using partial least squares structural equation modelling (PLS-SEM) with bootstrapping to assess measurement quality, direct associations, and indirect associations. The results indicate that all hypothesised relationships are positive and statistically significant. Enforcement efficacy shows the strongest association with accommodation value, regulatory fairness shows the strongest association with governance trust, and both accommodation value and governance trust are positively associated with destination loyalty. The indirect results further suggest that accommodation value and governance trust are important explanatory pathways linking policy perceptions with loyalty. This study contributes by integrating governance-based and marketing-based mechanisms in a single tourist-centred model and by showing how STR regulation is associated with destination loyalty through value and trust evaluations in Bali.